Characterization of local and peripheral immune system in pregnant and nonpregnant ewes. (8th July 2021) - Quirke, Laurel D; Maclean, Paul H; Haack, Neville A; Edwards, Sara J; Heiser, Axel; Juengel, Jennifer L
Abstract: Modulation of the immune system is known to be important for successful pregnancy but how immune function might differ between the lymph nodes draining the reproductive tract and peripheral lymph nodes is not well understood. Additionally, if immune system changes in response to the presence of an embryo during early pregnancy, and if this response differs in local versus peripheral immune tissue, has not been well characterized. To address these questions, we examined expression of genes important for immune function using NanoString technology in the ampulla and isthmus of the oviduct, endometrium, lymph nodes draining the reproductive tract (lumbo-aortic and medial iliac) as well as a peripheral lymph node (axillary), the spleen, and circulating immune cells from ewes on day 5 of the estrous cycle or pregnancy. Concentrations of estradiol and progesterone in plasma were also determined. Principal component analysis revealed separation of the local from the peripheral lymph nodes (MANOVA P = 3.245e-08, R 2 = 0.3) as well as separation of tissues from pregnant and nonpregnant animals [lymph nodes (MANOVA P = 2.337e-09, R 2 = 0.5), reproductive tissues (MANOVA P = 2.417e-14, R 2 = 0.47)]. Nine genes were differentially ( FDR < 0.10) expressed between lymph node types, with clear difference in expression of these genes between the lumbo-aortic and axillary lymph nodes. Expression of these genes in the medial iliac lymph node was not consistently different to either the axillary or the lumbo-aortic lymph node. Expression of IL10RB was increased (FDR < 0.05) by 24% in the reproductive tissue of the pregnant animals compared to nonpregnant animals. Analysis of gene categories revealed that expression of genes of the T-cell receptor pathway in reproductive tract tissues was associated ( P < 0.05) with pregnancy status. In conclusion, assessment of gene expression of reproductive and immune tissue provides evidence for a specialization of the local immune system around the reproductive tract potentially important for successful establishment of pregnancy. Additionally, differences in gene expression patterns in reproductive tissue from pregnant and nonpregnant animals could be discerned as early as day 5 of pregnancy. This was found to be associated with expression of genes important for T-cell function and thus highlights the important role of these cells in early pregnancy.